An update on the diagnosis and management of Budd–Chiari syndrome. (December 2012) - MacNicholas, Ross; Olliff, Simon; Elias, Elwyn; Tripathi, Dhiraj
Budd–Chiari syndrome is a rare disorder caused by hepatic venous outflow obstruction and resulting hepatic dysfunction. Despite a lack of prospective randomized trials, much progress has been made in its management over the last 20 years. The main goals of treatment are to ameliorate hepatic congestion and prevent further thrombosis. The selective use of anticoagulation, vascular stents, transjugular intrahepatic portosystemic stent-shunt and liver transplant has resulted in a significant increase in survival. The diagnosis, initial management and long-term follow-up of patients with Budd–Chiari syndrome is reviewed. The concept of individualization of treatment and a stepwise approach to invasive procedures is also discussed.